Consumer valuation of improved rice parboiling technologies in Benin - Demont, M.; Zossou, E.; Rutsaert, Pieter; Ndour, M.; Mele, P. van; Verbeke, W. (Elsevier, 2012)
In Benin, traditional parboiling is still widely practiced among rice processors, resulting in inferior grain quality. A new parboiler was introduced to improve the milling yield and intrinsic quality of local rice. We conducted Vickrey second price auctions to elicit rural Beninese consumers' willingness to pay for rice obtained through the new parboiler and two locally innovated parboilers. The individual auctions were followed by a group discussion during which consensus was reached on socially acceptable prices. Relative to traditionally parboiled rice, consumers were willing to pay price premiums of 9–13% for rice obtained through a local parboiler using a container of which the bottom is a perforated metal, 27% for rice obtained through a local parboiler using wooden sticks at the bottom of the pot, and 25–34% for rice parboiled through the improved parboiler. Bids were influenced by the presentation order of the products according to perceived quality. Bids were also higher when participants had been informed on the benefits of improved parboiling techniques, which is a crucial insight for developing marketing and communication strategies for this improved quality product. Group bids were not significantly different from individual bids which suggests that the latter are within the range of socially acceptable prices defined through group consensus.